Management Science Foundations and Innovations - Machado, Carolina; Davim, J. Paulo (Management and Industrial Engineering,, 2019)
This book presents the skills required in business and management careers. The management tools provided within this text can be very useful for beginners in the study of management area, as well as to those pursuing a managerial career in different types of organization. It serves as a refreshment in the management sciences foundations. Subjects such as accounting, marketing, human resources, operations, finance are treated in detail, giving the reader the background that can be applied to a variety of real world business situations. The book also covers the latest developments in management research activity, promoting discussion and the exchange of information on principles, strategies, models, techniques, methodologies and applications in the management and business area.